Acromioclavicular Septic Arthritis Caused by Veillonella parvula - Marc Prod’homme; Gilles Pfander; Patricia Pavese; Alexandre Cech; Islam Abouelnaga; Lionel Helfer (Case Reports in Orthopedics)
We hereby report the case of a primary acromioclavicular septic arthritis caused by Veillonella parvula. This bacteria is rare as a pathogen but is well known as a commensal of the lungs, vagina, mouth, and gastrointestinal tract of humans. However, it may turn as an opportunistic pathogen. It was isolated in blood culture and confirmed in biopsy specimen. The patient had complete recovery after surgical washout with second look at postoperative day two and targeted antibiotic treatment.